T Tingkat Pengetahuan Masyarakat Tentang Penyakit Tuberkulosis di Kelurahan Rintis Pekanbaru: Level of Public Knowledge about Tuberculosis at Rintis Village Pekanbaru - erniza - pratiwi; Nouval Zamra (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2022)
Research on the level of public knowledge about tuberculosis was conducted in Rintis Village, Pekanbaru City. This study aims to determine the level of public knowledge about tuberculosis in Rintis Village, Pekanbaru City. This study uses an observational method that is descriptive analytic using a cross sectional design through filling out questionnaires. The sampling technique in this study was carried out by non probability sampling with a purposive sampling method. The sample that became this study was 100 respondents who met the inclusion criteria. Research respondents who met the inclusion criteria were given a questionnaire which was then filled in by the respondent. Then the data is processed and analyzed by researchers. Based on the results of the study, it shows that people who have high knowledge are as much as 47%, people who have sufficient knowledge are as many as 32% and people who have low knowledge are as much as 21%. High knowledge is dominated by respondents with an age range of 56-65 years, female gender, high education (college) and secondary, and civil servant occupations.